A further family of Stromme syndrome carrying CENPF mutation. Issue 6 (13th April 2017) - Ozkinay, Ferda; Atik, Tahir; Isik, Esra; Gormez, Zeliha; Sagiroglu, Mahmut; Sahin, Ozlem Atan; Corduk, Nergul; Onay, Huseyin
Abstract : Stromme syndrome is a rare genetic disorder characterized by microcephaly, anterior ocular chamber anomalies, and "apple peel" type jejunal atresia. Here, we report a Stromme syndrome family with two affected siblings with a homozygous truncating frameshift mutation in CENPF . A 3‐month‐old girl was hospitalized due to prenatally diagnosed microcephaly, microphthalmia, and dysmorphological features. The history of a previous child with the same findings in addition to "apple peel" intestinal atresia had been noted. Regarding the clinical features of both affected siblings, a diagnosis of Stromme syndrome was established. Exome‐sequencing of these two cases showed the homozygous mutation (c.5912_5913insA)/(p.T1974Nfs*9) in CENPF . While confirmation of this gene being responsible for Stromme syndrome was pending our results, Filges et al. reported that CENPF was indeed underlying the reason for Stromme syndrome. This is the second case report identifying CENPF mutation as the cause of Stromme syndrome.